Optimal Design Method for Vessel-Bridge Collision Based on Life-Cycle Theory - Tao Fu; Kai Wang; Ye Zhou; Xiaoqian Ren; Zhixin Zhu; Yan Li; Yue Sun; Lingxiao Meng (Advances in Materials Science and Engineering)
As structures crossing waterways, bridges are obstacles to vessels. Vessel-bridge collisions are inevitable. They not only involve the safety of vessel passage but also seriously affect the safe operation of bridges. Vessel-bridge collisions cause not only huge economic losses and casualties but also severe political and environmental losses. Vessel collision safety of existing and new bridges is one of the key technical problems that engineers and bridge managers must solve. Comprehensive consideration of vessel-bridge collision risk loss and structural performance in the design stage to achieve optimal cost over the life cycle is an important aspect of bridge design. Based on the current life-cycle design theory of engineering structures, this paper proposes a theoretical framework for vessel-bridge collision optimization design based on the life cycle, which includes three parts: vessel-bridge collision probability analysis, vessel-bridge collision vulnerability analysis, and vessel-bridge collision hazard. Taking the minimum cost of the bridge structure in the design service life period as the objective function, the optimization design model and design process of vessel-bridge collision based on whole life are established, and the key problems to be solved in each part are expounded.